2022
DOI: 10.3390/electronics11172768
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Signal Interference Regularity of Single-Frequency Electromagnetic Radiation to Stepped-Frequency Radar

Abstract: When typical radar equipment is subjected to single-frequency electromagnetic radiation, the radar display interface forms a pseudo-signal, resulting in the misjudgment of real targets. Based on the working principle of stepped-frequency radar ranging, the effect mechanism of radar equipment pseudo-signal interference is revealed. Taking a Ku band stepped-frequency ranging radar as the test object, the pseudo-signal interference effect test of single-frequency electromagnetic radiation is carried out in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In order to find out the distance of the "hill" type pseudosignal, ignoring the influence of the third exponential term in formula (16), formula ( 16) is normalized:…”
Section: Imaging Analysis Of the "Hill" Type Pseudo-signalmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to find out the distance of the "hill" type pseudosignal, ignoring the influence of the third exponential term in formula (16), formula ( 16) is normalized:…”
Section: Imaging Analysis Of the "Hill" Type Pseudo-signalmentioning
confidence: 99%
“…When the interference field strength is strong, the pseudo-signal strength even exceeds the true echo signal strength, causing the radar to misjudge [13]. e authors in [14] pointed out that the single-frequency signal whose jamming frequency is located in the working frequency band of the radar can cause false alarm interference to the radar, but the target characteristics of the false alarm interference were not analyzed. e author in [15] believes that singlefrequency interference can cause pseudo-signal interference on the display interface of the FM CW radar, but the abovementioned documents do not involve radar multifrequency pseudo-signal interference.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the frequency hopping time t r and step frequency ∆f * are certain, the delay time t d in the acquisition moment t k = kt r + t d is uncertain, which will also make the false alarm signal uncertain. In the actual imaging, the actual value of the false alarm target distance should also be combined with the selection of the radar signal parameters (t r and ∆f * ) to determine whether there is distance redundancy and other related information [19][20][21]. If the radar signal parameters meet the tight constraint conditions, the unambiguous distance, corresponding to the sub-period of the transmitting signal is r τ = ct r /2.…”
Section: Intermodulation False Alarm Target Characteristicsmentioning
confidence: 99%
“…Research on the radar's false target is mostly aimed at information interference, and there is relatively less research on the non-information interference [15,16]. In the test of the radar EMI effect, it is found that when the interference frequency falls into the filter bandwidth, it will not only produce a blocking effect on the radar, but will also cause the radar to produce a false target response, which seriously affects the effective judgment of the battlefield situation [17,18]. In addition, the out-of-band dualfrequency EMI also causes the radar to produce a false target response similar to the in-band single frequency, therefore, it is necessary to study the radar's dual-frequency false target response mechanism.…”
Section: Introductionmentioning
confidence: 99%